UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR DIVERGEN SISWA KELAS VII-B SMP NEGERI 4 MADIUN MELALUI MODEL PEMBELAJARAN OPEN ENDED - Widiawati, Fithia Safira; Yohanes, Rudi Santoso (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
This research is aimed to describe the level of divergent reasoning through Open Ended model for the student of VII-B SMPN 4 Madiun. Divergent reasoning is basically one of the student`s abilities that plays a significant role in mathematics. Due to the development of divergent reasoning, hence, it needs the appropriate approach – open ended approach. The use of implementation cycles (Hopkins) in this research is indispensible. In this case, implementation cycles consists of rearranging, planning, observation, reflection, and re-planning. The data in this research consist of two factors, namely, the students` divergent reasoning and the teacher`s ability in applying Open Ended. Furthermore, data are taken through the test model. Thus, the application of observation model is used to measure the teacher`s ability in applying Open Ended. Besides, in order to measure the level of divergent reasoning, the teacher provides an essay. Moreover, the essay here adheres to some indicators – think smoothly, think flexibly, and think creatively. Furthermore, the observation method is used to gain the accurate data that proves the teacher`s ability in teaching. Hence, field research is applied as the technique of data collecting. At last, the data analysis proves that the Open Ended is not sufficient to increase the students` divergent reasoning by depending on only two cycles. Key Words : Open Ended, Divergent Thingking